Extended Antibiotic Prophylaxis May Be Linked to Lower Peri-prosthetic Joint Infection Rates in High-Risk Patients: An Evidence-Based Review. Issue 3 (October 2019) - DeFrancesco, Christopher J.; Fu, Michael C.; Kahlenberg, Cynthia A.; Miller, Andy O.; Bostrom, Mathias P.
In 2018, Inabathula et al. published the results of a historical control study examining 90-day peri-prosthetic joint infection (PJI) rates at a single center before and after the institution of an extended post-operative oral antibiotic protocol for high-risk total hip arthroplasty (THA) and total knee arthroplasty (TKA) patients. In the study, "Extended Oral Antibiotic Prophylaxis in High-Risk Patients Substantially Reduces Primary Total Hip and Knee Arthroplasty 90-Day Infection Rate" ( J Bone Joint Surg Am . 2018;100[24]:2103–2109), the authors considered any one of several patient-related criteria—including diabetes, a body mass index of 35 kg/m 2 or higher, or active smoking—as sufficient to designate a patient "high risk" for PJI. Before the extended antibiotic therapy protocol was instituted, PJI rates for primary THA and TKA in the high-risk subgroup were 4.3% and 2.1%, respectively. After it was instituted, the respective rates dropped to 1.1% and 0.4%, comparable to those seen in the non-high-risk patients treated using standard peri-operative prophylaxis. After adjusting for patient factors, regression analysis showed that high-risk patients receiving only peri-operative antibiotics were more likely to develop PJI than high-risk patients receiving the extended antibiotic protocol. Although these results suggest possible benefits of extended antibiotic prophylaxis in arthroplasty, methodologic limitations and inadequate discussion of potential drawbacks of widespread adoption of such protocols limit the impact of the findings. Future research is warranted to more narrowly define risk factors for PJI and to demonstrate the safety and efficacy of extended antibiotics in reducing the long-term burden of PJI.